Continuing to Make Sense of a Narrative Conception of Hope - LeMay, Lenora M. (Alberta Journal of Educational Research, 2021)
In this autobiographical narrative inquiry, I continued to make sense of a Deweyan-inspired narrative conception of hope (LeMay, 2014). I started with a remembered story that occurred on a First Nation shortly after I commenced working at a post-secondary institution. Following that, I shared stories that led me to wonder about a Deweyan-inspired narrative conception of hope and then what I learned in a dissertation with two teachers as we worked with a Deweyan-inspired narrative conception of hope. From there, I unpacked the remembered story, using the three learnings that resonated in my sensemaking with the two teachers. Lastly, I reflected on how this inquiry inspired me to continue to make sense of students’ storied experiences of working with a narrative pedagogy of hope (LeMay, 2014) in relation to their well-being. Key words: a narrative conception of hope, narrative inquiry, autobiographical narrative inquiry, hope-focused practices and strategies, making hope visible and accessible Dans cette enquête narrative autobiographique, j'ai continué à donner du sens à une conception narrative de l'espoir inspirée par Dewey (LeMay, 2014). J'ai commencé par me souvenir d'une histoire qui s'est produite sur une Première Nation peu après que j'ai commencé à travailler dans un établissement postsecondaire. Ensuite, j'ai partagé les histoires qui m'ont amenée à m'interroger sur une conception narrative de l'espoir inspirée par Dewey, puis ce que j'ai appris dans le cadre d'une dissertation avec deux enseignants alors que nous travaillions avec une conception narrative de l'espoir inspirée par Dewey. Ensuite, j'ai décortiqué l'histoire dont je me souviens en utilisant les trois apprentissages qui ont résonné dans ma recherche de sens avec les deux enseignants. Enfin, j'ai réfléchi à la façon dont cette enquête m'a inspirée pour continuer à donner du sens aux expériences narratives des élèves qui travaillent avec une pédagogie narrative de l'espoir (LeMay, 2014) en relation avec leur bien-être. Mots-clés : une conception narrative de l'espoir, une enquête narrative, une enquête narrative autobiographique, des pratiques et des stratégies axées sur l'espoir, rendre l'espoir visible et accessible